Changes in setting time of alginate impression material with different water temperature - Decky J. Indrani; Niti Matram (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2013)
Background: Previous studies showed that setting process of alginates can be influenced by temperature. Purpose: To determine the changes in setting time due to differences in water temperature and to determine the correlation between water temperature and the setting time. Methods: Seven groups of dough alginate were prepared by mixing alginate powder and water, each using a temperature between 13° C–28° C with a interval of 2.5° C. A sample mold (Θ = 30 mm, t = 16 mm) was placed on a flat plate and filled with doug alginate. Immediately the flat end of a polished acrylic rod was placed in contact with the surface of dough alginate. Setting time of alginat was measured from the starting of the mix to the time when the alginate does not adhere to the end of the rod. Setting time alginate data were analyzed using one way ANOVA, LSD and Pearson. Results: Setting time of alginate with water temperature between 13° C–28° C were 87 to 119.4 seconds and were significantly different (p < 0.01). The setting time between group were also significantly different (p<0.01). There was an inverse correlation between water temperature and the setting time (r = -0.968). Conclusion: Water temperature between 13° C–28°C with a difference of 2.5° C produced significant differences in alginate setting time; the lower the water temperature being used the longer the setting time was produced.Latar belakang: Penelitian-penelitian sebelumnya menunjukkan bahwa proses pengerasan alginat dapat dipengaruhi oleh suhu. Tujuan: Mengetahui perubahan waktu pengerasan alginat akibat perbedaan suhu air serta mengetahui hubungan antara suhu air dan waktu pengerasan. Metode: Tujuh kelompok adonan alginat yang dipersiapkan dengan mencampur bubuk alginat dan air, masingmasing menggunakan suhu antara 13°C–28° C dengan interval 2,5° C. Pengukuran waktu pengerasan alginat dilakukan sesuai dengan spesifikasi ADA no.18. Sebuah cetakan sampel terbuat dari pralon berbentuk cincin (Θ = 30 mm, t = 16 mm) ditempatkan di atas plat datar dan dipenuhi dengan adonan alginat. Pengukuran waktu pengerasan dilakukan segera dengan menyentuhkan ujung datar batang akrilik yang telah dipoles di permukaan adonan alginat. Waktu pengerasn alginat diukur dari awal pencampuran bubuk alginat dan air sampai dengan waktu awal ketika alginat tidak melekat di ujung batang. Data waktu pengerasan yang diperoleh dianalisis menggunakan uji statistik One-way Anova, LSD dan Pearson. Hasil: Suhu air antara 13° C–28° C telah menghasilkan waktu-waktu pengerasan alginat 87 detik hingga 119,4 detik yang berbeda signifikan (p < 0,01). Waktu pengerasan antar grup juga menunjukkan perbedaan signifikan (p<0,01). Antara suhu air dan waktu pengerasan alginat terdapat hubungan terbalik (r=-0,968). Kesimpulan. Suhu air antara 13°C–28°C dengan interval 2,5° C menghasilkan perbedaan waktu pengerasan alginat; makin rendah suhu air yang digunakan untuk mencampur makin panjang waktu pengerasan alginat.